Markers for Characterization of Bone Marrow Multipotential Stromal Cells - Sally A. Boxall; Elena Jones (Stem Cells International)
Given the observed efficacy of culture-expanded multipotential stromal cells, also termed mesenchymal stem cells (MSCs), in the treatment of graft-versus host and cardiac disease, it remains surprising that purity and potency characterization of manufactured cell batches remains rather basic. In this paper, we will initially discuss surface and molecular markers that were proposed to serve as the indicators of the MSC potency, in terms of their proliferative potential or the ability to differentiate into desired lineages. The second part of this paper will be dedicated to a critical discussion of surface markers of uncultured (i.e., native) bone marrow (BM) MSCs. Although no formal consensus has yet been reached on which markers may be best suited for prospective BM MSC isolation, markers that cross-react with MSCs of animal models (such as CD271 and W8-B2/MSCA-1) may have the strongest translational value. Whereas small animal models are needed to discover the in vivo function on these markers, large animal models are required for safety and efficacy testing of isolated MSCs, particularly in the field of bone and cartilage tissue engineering.